2019
DOI: 10.22146/ijc.34189
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Carbon from Merbau Wood (<i>Intsia spp.</i>) by Microwave Method as Ni Catalyst Support for α-Cellulose Hydrocracking

Abstract: Synthesis of mesoporous carbon from Merbau wood (Intsia spp.) waste by microwave method as nickel catalyst support for α-cellulose hydrocracking had been carried out. The Merbau wood sawdust was carbonized at 800 °C to produce C800 and the C800 was treated by microwave irradiation (399 W) for 5 min to produce C800MW. The Merbau wood flakes, which were only treated by microwave irradiation (399 Watts) for 30 min produced CMW. Wet impregnation technique was carried out to disperse the Ni metal (1.0, 1.5, and 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It can assist the loading process of active catalyst species, facilitate good reactant transport, and expand the temperature range in reaction applications. It is known that mesoporous carbon can be impregnated well with various types of metals for multiple applications such as Ag [19][20], Pd [20], Ni [21][22], Co [23], Ru [24], and Cu [25]. In addition, mesoporous carbon is also a potential material to be used as a CO2 adsorbent [26][27].…”
Section: ■ Introductionmentioning
confidence: 99%
“…It can assist the loading process of active catalyst species, facilitate good reactant transport, and expand the temperature range in reaction applications. It is known that mesoporous carbon can be impregnated well with various types of metals for multiple applications such as Ag [19][20], Pd [20], Ni [21][22], Co [23], Ru [24], and Cu [25]. In addition, mesoporous carbon is also a potential material to be used as a CO2 adsorbent [26][27].…”
Section: ■ Introductionmentioning
confidence: 99%
“…The significant constitutive fractions, in the term of weight of these lignocellulose materials as the use as activated carbon precursor, are the hemicellulose, cellulose, and lignin. Merbau wood as lignocellulose materials has been known to have potential as a carbon 1232 (2022) 012001 IOP Publishing doi:10.1088/1757-899X/1232/1/012001 2 precursor [13]. Because of the difference in reactivity between these components during the pyrolysis step, the study of their carbonization is rather complicated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that transition metals-modified dispersed to porous materials are used as a catalyst in hydrocracking reaction [18][19][20]. The benefits of this type of catalyst include the inclusion of metal acid sites and the avoidance of metal agglomeration due to the dispersal of transition metals into the porous system such as mesoporous silica [19], MCM-41 [21], and mesoporous carbon [13,18]. In this work, the main study was to investigate the catalytic performance of nickel oxide/carbon catalysts on the hydrocracking of pyrolyzed α-cellulose as a model of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that microwave irradiation was used in the chemical process due to the simple and clean method with high-efficiency energy. Nanoparticle materials have been prepared by microwave-assisted methods with uniform, small, narrow size distributions and high crystalline orders in comparison with nanoparticle synthesized by the conventional heating method [19][20][21]. Acid modification of material is usually conducted under a reflux condition with high temperature and long reaction time under an oil bath.…”
Section: ■ Introductionmentioning
confidence: 99%